2007
DOI: 10.1093/nar/gkm139
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the third KH domain of human poly(C)-binding protein-2 in complex with a C-rich strand of human telomeric DNA at 1.6 A resolution

Abstract: KH (hnRNP K homology) domains, consisting of ∼70 amino acid residues, are present in a variety of nucleic-acid-binding proteins. Among these are poly(C)-binding proteins (PCBPs), which are important regulators of mRNA stability and posttranscriptional regulation in general. All PCBPs contain three different KH domains and recognize poly(C)-sequences with high affinity and specificity. To reveal the molecular basis of poly(C)-sequence recognition, we have determined the crystal structure, at 1.6 Å resolution, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…Crystal structures of the KH3 domain from hnRNP K in its free and DNAbound form and the KH3 domain from PCBP1 in its free form have also been published (Backe et al2005;Sidiqi et al 2005). We have also determined the crystal structure of PCBP2 KH3 in complex with a 7-nt human telomeric DNA (Fenn et al 2007). Interestingly, the kind of dimerization we observed in PCBP2 KH1 structures was not observed in the KH3 domain structures.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Crystal structures of the KH3 domain from hnRNP K in its free and DNAbound form and the KH3 domain from PCBP1 in its free form have also been published (Backe et al2005;Sidiqi et al 2005). We have also determined the crystal structure of PCBP2 KH3 in complex with a 7-nt human telomeric DNA (Fenn et al 2007). Interestingly, the kind of dimerization we observed in PCBP2 KH1 structures was not observed in the KH3 domain structures.…”
Section: Discussionmentioning
confidence: 60%
“…The KH1 + KH2 construct yielded excellent quality NMR spectra (Fig. 5A) (Fenn et al 2007). Positively charged, negatively charged, and uncharged hydrophilic and hydrophobic residues are colored in blue, red, yellow, and green, respectively; glycines are in white.…”
Section: Nmr Evidence For Kh1-kh2 Interactionmentioning
confidence: 97%
“…PCBP1 protein has been identified as the most specific binding protein for telomeric C-rich DNA and may be presented in the human telomere-telomerase complex 42,43 . We also observed removal of PCBP1 protein from telomere after treatment with SWNTs.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the cause of telomere uncapping, we investigated the effect of SWNTs on the localization of TRF2 and POT1, two telomeric proteins that can induce telomere dysfunction and evoke DNAdamage signaling when their levels are reduced at telomeres 1,34,35 . Furthermore, we also studied the effect of SWNTs on the localization of PCBP1 (poly-(C) binding protein 1) at telomere, which has been identified as a specific telomere C-rich strand binding protein, and may have an important role in telomere maintenance 42,43 . Confocal microscopy showed that SWNTs specifically delocalized TRF2, POT1 and PCBP1 from TRF1 foci in HeLa cells after 2 weeks of treatment (Fig.…”
Section: Dna-damage Response Triggered By Swnts Occurred At Telomerementioning
confidence: 99%
“…For most samples, the final NMR buffer contains 50 mM deuterated sodium acetate (pH 5.4), 2 mM dithiothreitol, 0.1 M EDTA, in either 90% H 2 O/10% D 2 O or 100% D 2 O. Preparation of the KH3 construct has also been described previously (27). For the full-length construct, protein expression was induced with 0.1 mM isopropyl-␤-D-thiogalactopyranoside at A 600 ϭ 0.6 -0.8 at 10°C for 48 h before harvest.…”
Section: Methodsmentioning
confidence: 99%